2015
DOI: 10.1371/journal.pone.0127230
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of OSM on MC3T3-E1 Osteoblastic Cells in Simulated Microgravity with Radiation

Abstract: Bone deterioration is a challenge in long-term spaceflight with significant connections to patients experiencing disuse bone loss. Prolonged unloading and radiation exposure, defining characteristics of space travel, have both been associated with changes in inflammatory signaling via IL-6 class cytokines in bone. While there is also evidence for perturbed IL-6 class signaling in spaceflight, there has been scant examination of the connections between microgravity, radiation, and inflammatory stimuli in bone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 86 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…Our studies with breast cancer patients showed that high serum levels of OSM and IL-6 are correlated, and OSM has been shown to induce IL-6 expression in smooth muscle cells, osteoblasts, and astroglioma cells [49, 57, 58]. This prompted us to investigate whether OSM signals mammary tumor cells to increase IL-6 expression in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Our studies with breast cancer patients showed that high serum levels of OSM and IL-6 are correlated, and OSM has been shown to induce IL-6 expression in smooth muscle cells, osteoblasts, and astroglioma cells [49, 57, 58]. This prompted us to investigate whether OSM signals mammary tumor cells to increase IL-6 expression in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…The question of whether low-dose radiation response is modulated by microgravity is an important aspect of risk assessment that has received little attention in the literature (32,33). The objective of the current study was to use a ground-based animal model for spaceflight, combining radiation and HLU simultaneously for 21 days, to assess FIG.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this finding remain unclear. However, others have observed similarly divergent responses to radiation and simulated microgravity in osteoblast inflammatory signaling (32) and bystander signaling in plants (43). HLU in combination with LDR radiation may induce apoptotic protein expression and apoptosis with different timing compared to each stressor alone.…”
Section: Simulated Spaceflight Induces Oxidative Damage In Brainmentioning
confidence: 95%
“…OSM supplementation upregulated collagen α1(I) and osteocalcin genes but had no significant effect on sclerostin transcription. RCCS downregulated collagen α1(I) and osteocalcin while upregulating sclerostin 38 .…”
Section: Discussionmentioning
confidence: 98%